2003
DOI: 10.1002/pola.10974
|View full text |Cite
|
Sign up to set email alerts
|

Segmented poly[2‐methoxy‐5‐(2‐ethylhexyloxy)‐1,4‐phenylene vinylene] via xanthate and dithiocarbamate precursors: A comparative study of thermal eliminations

Abstract: Segmented poly[2-methoxy-5-(2-ethylhexloxy)-1,4-phenylene vinylene] (MEH-PPV)-x's, which contain conjugated segments of varying lengths that are interspersed by nonconjugated units along the polymer backbone, were synthesized by selective thermal elimination of precursors containing controlled amounts (x) of a thermally labile group, namely, xanthate or dithiocarbamate (DTC). These precursors were in turn synthesized by competitive nucleophilic substitution of the Wessling polyelectrolyte with varying molar fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…15 %). [17] A similar trend was observed in solid-state polymer films. In the blend of the two polymers the PL of the LC phase was completely quenched and the PL of the HC phase was enhanced.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…15 %). [17] A similar trend was observed in solid-state polymer films. In the blend of the two polymers the PL of the LC phase was completely quenched and the PL of the HC phase was enhanced.…”
Section: Resultssupporting
confidence: 61%
“…1a) have recently been synthesized by selective elimination of side groups of a suitable precursor containing two types of eliminable groups, namely, diethyl dithiocarbamate (DTC) and methoxy groups. [17] Selective elimination of DTC groups, leaving the methoxy groups unaffected, leads to the generation of truncated MEH-PV oligomeric units, of varying conjugation lengths, within each polymer chain. This approach provides a It is demonstrated that the energy transfer from low-conjugated (LC) poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEHPPV) to high-conjugated (HC) MEHPPV, coupled with significant electron transfer from HC-MEHPPV to an acceptor species, offers a viable route for an efficient photodiode over a wide spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble PPVs can be obtained by heating the precursor polymer 24b in 1,2-dichlorobenzene at 175 • C. Photoluminescence of PPV films suggests that the PPV from this dithiocarbamate precursor route may have slightly more defects than that from the sulfinyl precursor 20. The dithiocarbamate precursor route is also useful for preparation of segmented PPV derivatives via controlled elimination [54]. …”
Section: The Wessling Methodsmentioning
confidence: 99%
“…Figure 7 shows FTIR spectra of the graft copolymer before and after reacting it with the fullerene. The spectrum shows two new weak transmission bands at 528 cm −1 and 577 cm −1 , which represent the characteristic of the fullerene‐bonded polymers 18. In addition, UV–vis absorption spectra of the product from ATRA (Fig.…”
Section: Resultsmentioning
confidence: 97%